Analysis of Chili Inventory at Vegetable Traders at Karawang New Market - Deka Putri Lestari; Dedi Mulyadi; Santi Pertiwi Hari Sandi (International Journal of Economics and Management Research, 2025)
This study aims to analyze the source of supply, quantity of inventory, price, quality, and handling of chili inventory at vegetable traders in Pasar Baru Karawang. The research method used is descriptive qualitative with random sampling technique on three traders. The results of the study indicate that the main source of supply comes from Cikopo, Cibitung and Bandung, with daily orders via WhatsApp and cash or transfer payments. The amount of chili inventory fluctuates significantly, especially during the big day period, Mr. Edi's inventory increases to 50-60 kg when demand is high. Normal stock ranges from 30-40 kg per day. Mr. Deni increases his chili inventory to 70 kg when demand is high, with a normal stock of 20-40 kg per day, while Mr. Dendi's inventory increases to 230 kg when demand is high with a normal stock of 150-160 kg per day. Chili prices fluctuate due to weather and demand at certain moments such as Eid al-Fitr, Eid al-Adha, Christmas and New Year. The highest price fluctuation occurs in January with a peak price of IDR 120,000/kg due to the new year and high rainfall. While the lowest price occurred in November at Rp 20,000/kg due to declining consumer demand and poor chili quality due to high rainfall. Traders implement the FIFO system to maintain quality and implement safety stock and re-orders to avoid stock shortages . The conclusion shows that efficient inventory management is very important to deal with market fluctuations .